THE NECESSITY OF REPLACING THE TERM «ՏՈԿՈՍ» (―PERCENT‖) IN ARMENIAN MATHEMATICAL TERMINOLOGY - Poghosyan, G.; Mkrtchyan, A. (SUSh Scientific Proceedings, 2025)
In the 21st century, the average person, regardless of their field of activity, needs a more extensive reserve of mathematical knowledge than before. One of such an essential knowledge is the precise understanding and calculation of the concept of ―percent‖, which forms the basis of financial literacy. While the philosophy of lifelong learning in modern civilization emphasizes that it is never late to learn and acquire new knowledge, fundamental mathematical concepts, including the notion of ―percent‖, must be introduced in schools and reinforced to ensure proper comprehension. Students often struggle to grasp the concept of ―percent‖. This situation needs to be changed. A study was conducted, and our experimental results revealed that replacing the use of the symbol ―%‖ and its verbal reading as ―percent‖ with terms that reflect the essence of the concept, such as ―onehundredth‖, ―hundredth part‖, or similar expressions, significantly improves the level of understanding. The experimental group demonstrated notably higher success rates in solving problems. This indicates that the term ―percent‖, which has been synthetically integrated into the Armenian mathematical vocabulary, is cognitively less intuitive and harder to grasp compared to terms like ―one-hundredth‖ that directly convey its essence and meaning. It is proposed to replace the term ―percent‖ with ―one-hundredth‖ or ―hundredth part‖.